Relação entre o índice de vulnerabilidade a saúde e a distribuição espacial da dengue em Pedro Leopoldo - MG, 2009 a 2011 - Rachel Lage Brito (2012)
In Pedro Leopoldo (Minas Gerais, Brazil), dengue is one of the most frequently reported diseases. The index of vulnerability to health (IVS) is a composite indicator that combines different variables such as sanitation, housing, income, education, health and social factors. A correlation between the occurrence of dengue and IVS becomes more efficient the location of points and priorities for deployment of combat actions. This study aimed to look for this correlation and spatial analysis of dengue in Pedro Leopoldo, between 2009 and 2011. However, the IVS is not presented as a better tool to explain the incidence of dengue in this city during the study period. The sites considered by IVS with greater vulnerability to health problems were those with lower incidence of dengue. Only in 2011 there was an inverse correlation between the status of the IVS and the incidence rates. This also occurred between status of IVS and the Bayesian local rates. When the IVS was classified, there was a significant inverse correlation with the Bayesian local rates in all years involved in this study, showing that the form of categorization of IVS influenced the results of the correlation. Sites with greater vulnerability to health sectors were located in Lagoa de Santo Antônio, north of the city. The sectors with the lowest vulnerability to health was in downtown of Pedro Leopoldo.